Telisik determinan kinerja auditor - Sulistyawati, Ardiani Ika; Rachmawati, Ika Anis; Santoso, Aprih (Indonesia Accounting Journal, 2019)
This study aims to test and obtain empirical evidence on the influence of accountability, competence, task complexity, and organizational culture on auditor performance. Respondents in this study are auditors who work at the Audit Board and Development (BPKP) Representative of Central Java Province. The number of questionnaires distributed was 90 questionnaires from 5 sections of BPKP Central Java Provincial Representative Office, but only 80 questionnaires are used. Sampling the results showed that no deviations of classical assumptions were found. This study uses t test of multiple regression with Accountability, Competence, Task Complexity, and Organizational Culture as independent variables and Performance of Auditors as dependent variable. The results of regression shows that coefficient of determination is 0,540 which means 54% auditor performance can be influenced by four independent variables, and 46% influenced by other variables.